Motile Cilia on Kidney Proximal Tubular Epithelial Cells Are Associated With Tubular Injury and Interstitial Fibrosis - Eymael, Jennifer; Willemsen, Brigith; Xu, Joyce; Mooren, Fieke; Steenbergen, Eric; Wetzels, Jack F.; Dijkman, Henry; Jansen, Jitske; Van der Vlag, Johan; Smeets, Bart (Frontiers in Cell and Developmental Biology, 2022)
It is well established that mammalian kidney epithelial cells contain a single non-motile primary cilium (9+0 pattern). However, we noted the presence of multiple motile cilia with a central microtubular pair (9+2 pattern) in kidney biopsies of 11 patients with various kidney diseases, using transmission electron microscopy. Immunofluorescence staining revealed the expression of the motile cilia-specific markers Radial Spoke Head Protein 4 homolog A, Forkhead-box-protein J1 and Regulatory factor X3. Multiciliated cells were exclusively observed in proximal tubuli and a relative frequent observation in human kidney tissue: in 16.7% of biopsies with tubular injury and atrophy (3 of 18 tissues), in 17.6% of biopsies from patients with membranous nephropathy (3 of 17 tissues) and in 10% of the human kidney tissues derived from the unaffected pole after tumour nephrectomy (3 of 30 tissues). However, these particular tissues showed marked tubular injury and fibrosis. Further analysis showed a significant relation between the presence of multiciliated cells and an increased expression of alpha-smooth-muscle-actin (p-value < 0.01) and presence of Kidney-injury-molecule-1 (p-value < 0.01). Interestingly, multiciliated cells co-showed staining for the scattered tubular cell markers annexin A2, annexin A3, vimentin and phosphofructokinase platelet but not with cell senescence associated markers, p16 and degradation of lamin B. In conclusion, multiciliated proximal tubular cells with motile cilia are frequently observed in kidney biopsies and associated with tubular injury and interstitial fibrosis. These data suggest that proximal tubular cells are able to transdifferentiate into multiciliated cells.